Deconstruction of Meaning And Themes in Rini’s Song Aph-rodite: a Semiotic Approach by Roland Barthes (International Journal of Education and Literature, 2025)
This study examines the semiotic and mythological representation of song lyrics, taking RINI's "Aphrodite" as an example. Based on Roland Barthes' semiotics theory, this study examines the application of Greek mythology, specifically the character of Aphrodite, to convey love, beauty, and lust in the song. Qualitative descriptive approaches are used to examine the denotative, connotative, and mythological meanings inherent in the lyrics. The findings indicate that the song showcases Aphrodite both as a reference to Greek mythology and as an idealized figure of love and beauty in contemporary popular music. By way of metaphor, symbolism, and lyrical storytelling, RINI relates a story that intertwines personal emotion and cultural myth, demonstrating how antiquity's myths remain active in shaping contemporary creative work. The study emphasizes the use of music as a medium for rearticulating classical mythology in relation to depicting modern romantic ideals.